Synovial sarcoma of the larynx - Bhandari, Anita (Springer India, 1998)
A 23 years old male presented with a soft cystic mass in the left paralaryngeal space since 3 months. Indirect laryngoscopy revealed a bulging of the left lateral pharyngeal wall. Histopathologic al examination of the biopsy proved it to be a synovial sarcoma. The case is the seventh case reported in literature.